Les paillotes gitanes de vente de fruits et légumes à Montpellier, entre justice alimentaire et relégation - Gaëlla Loiseau; Coline Perrin; Gwenn Pulliat (EchoGéo, 2022)
Since the end of the 1970s, in summer, families from the Gypsy community have been selling fruit and vegetables in huts on the outskirts of Montpellier, particularly on roundabouts with heavy traffic, by mobilizing diversified supplies. The fact that these precarious sales spaces have been maintained for more than forty years testifies to the ability of these retailers to combine the interests of producers and consumers. They exploit a niche market and play a significant role in the local food system. The complex logistics that make up a large part of their activity reveal the mechanisms of relegation intertwined with the long-standing involvement of these families in the local circular economy. Their role in short food supply chains appears to be a form of resistance linked to issues of food justice.